Myocardial work in overweight and obesity: impact of sex and central haemodynamics. (14th October 2021) - Lindseth, K T; Gerdts, E; Midtboe, H; Pristaj, N; Cramariuc, D; Einarsen, E
Abstract: Background: Women with increased body mass index (BMI) have better left ventricular (LV) global longitudinal strain (GLS) than men. LV global myocardial work index (GWI) is a novel measure of myocardial function that adjusts for afterload and offers the opportunity to differentiate between early systolic dysfunction and elevated myocardial workload. Purpose: To investigate sex differences in myocardial work in women and men with increased BMI. Methods: Clinical and echocardiographic data from 467 participants (61% women, average age 47±9 years) with a BMI above 27 kg/m 2 and without cardiac disease was analysed. Central pulse wave analysis was assessed by applanation tonometry. GWI was calculated by GLS and post-echocardiography blood pressure (BP). Covariables of GWI were identified by linear regression analysis with collinearity tools. Results: Women had higher BMI (31.4 vs. 31.0 kg/m 2 ) and higher aortic augmentation pressure (12±7 vs. 8±6 mmHg), but lower clinic systolic BP (127±17 vs. 134±14 mmHg) compared to men (all P<0.05). Women also had higher LV GLS (20.0±2.8 vs. 18.8±2.8%) and GWI (2126±385 vs. 2047±389 mmHg%) (both P<0.05). In univariable regression analyses, higher GWI was significantly associated with higher age, clinic systolic BP, wall stress, ejection fraction, aortic augmentation pressure, left atrial size, and LV ejection time, and with lower waist circumference (all P<0.05), but not with BMI. In multivariable linear regression analyses, adjusting for these correlates, female sex was independently associated with higher GWI (Table 1, model 1). After additional adjustment for aortic augmentation pressure, the association between GWI and sex became non-significant (Table 1, model 2). Conclusions: Women with increased BMI have higher GWI compared to men, despite lower BP. Higher GWI in women is mainly explained by elevated workload due to higher central aortic stiffness. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Western Norwegian Regional Health Authorities